Pengaruh Penggunaan Layanan Financial Technology Terhadap Keberlangsungan Usaha Pelaku UMKM: Studi Kasus UMKM Kecamatan Medan Marelan - Sharzia Adewirza; Isra Hayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of the use of financial technology services on the business sustainability of MSMEs (Case Study of MSMEs in Medan Marelan District) both partially and simultaneously. This research approach is associative. The sample in this research was 30 Micro, Small and Medium Enterprises (MSMEs) in Medan Marelan District that use Financial Technology in the form of QRIS (Quick Response Code Indonesian Standard). QRIS (Quick Response Code Indonesian Standard) is available on the Dana, OVO, Shopee Pay, GoPay, mobile banking and other applications. Data collection techniques in research use observation, documentation and questionnaire techniques. The data analysis technique in this research uses a Simple Linear Analysis Test, Hypothesis Test (t Test). The research results show that partially the financial technology variable has a significant effect on the sustainability of Medan Marelan District MSMEs, as indicated by the t-test results being greater than t table (14,214>2,048) with a significant number of 0.01<0.05. The magnitude of the influence of 87.8% is shown through the R-Square calculation. Shows that the use of Financial Technology Services affects the sustainability of MSMEs by 87.8%.